From innovation to impact: Investigating the financial and sustainability outcomes of digital transformation in Saudi Arabia context - Attia, Eman Fathi; Enyah, Lyla Khalid; Othman, Mahdy Salah (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to discuss the digital transformation implications on firms’ financial performance. Digital transformation can support firms in the field of digitizing their business models. Practically in terms of standards operating procedures “SOPs”. Firms’ digitalization may have a beneficial impact on their financial performance by adopting different types of technologies that allow for the efficient use of resources and the reduction of cost, enabling the transformation of business models into sustainable ones within the circular and digitized economy. With huge potentials in improving firms’ performance and enhancing growth, digital transformation has raised much attention from firms worldwide. On the other hand, the high costs associated, and capital required with the transformation cannot be ignored. Few researches have looked into firms’ financial performance before and after adopting digital transformation, after examining the benefits and costs of digital transformation. This paper is about to give a complete analysis of the effect of digital technologies on the financial performance of firms, in an attempt to fill existing research gaps. With a random sampling method of stratification (with 30–50 companies), the study includes factory owners, brokers, service providers, and those within tourism and hospitality and have been randomly selected in order to get a diverse representation. The findings show that stable competitive advantage crazily leads to significant cost savings and highlights the subject of effective differentiation and position in the market. Firms that successfully exploit their competitive advantages effectively gain in profits due to the fact that they have simplified their processes and lowered their costs. Nevertheless, the financial concerns related to sustainability investments and monitoring improvements demonstrate low short-term benefits because of the absence of other influences that are the motivating factor of the production line. Sustainability projects, which are part of the companies’ strategic initiatives, are found to have a limited role in direct reduction in costs, and hence more research is required in the field to investigate their wider implications beyond cost-effectiveness. The research indicates that the application of dynamic innovations and market insights is of great importance for the achievement of a unique market advantage. Moreover, it gives room to explore more variables in order to conduct more in-depth studies on the interrelationships between environmental strategy practices, digital transformation, and financial outcomes. Therefore, future research can bridge corresponding gaps and new research directions for the better digital strategy implementation which generates improved financial results and long-term business success.